Implications of sex differences in immunity for SARS-CoV-2 pathogenesis and design of therapeutic interventions (2020)
Men present more frequently with severe manifestations of COVID-19 and are at higher risk for death. The underlying mechanisms for these differences between female and male individuals infected with SARS-CoV-2 are insufficiently understood. However, studies from other viral infections have shown that females can mount stronger immune responses against viruses than males. Emerging knowledge on the basic biological pathways that underlie differences in immune responses between women and men needs to be incorporated into research efforts on SARS-CoV-2 pathogenesis and pathology to identify targets for therapeutic interventions aimed at enhancing antiviral immune function and lung airway resilience while reducing pathogenic inflammation in COVID-19.